2021
DOI: 10.1136/openhrt-2021-001715
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K2—a neglected player in cardiovascular health: a narrative review

Abstract: Vitamin K2 serves an important role in cardiovascular health through regulation of calcium homeostasis. Its effects on the cardiovascular system are mediated through activation of the anti-calcific protein known as matrix Gla protein. In its inactive form, this protein is associated with various markers of cardiovascular disease including increased arterial stiffness, vascular and valvular calcification, insulin resistance and heart failure indices which ultimately increase cardiovascular mortality. Supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 120 publications
0
17
1
1
Order By: Relevance
“…Vitamin K 2 plays a role in cardiovascular health by regulating calcium homeostasis [ 20 ]. Vitamin K 2 regulates calcification by activating matrix Gla protein, which prevents vascular calcification, and growth arrest-specific 6, which affects vascular smooth muscle cell apoptosis and movement [ 21 ]. In the case that ABCG5/ABCG8 transports vitamin K 2 , defects in vitamin K 2 transport by ABCG5/ABCG8 may be associated with the progression of atherosclerosis in addition to cholesterol transport impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin K 2 plays a role in cardiovascular health by regulating calcium homeostasis [ 20 ]. Vitamin K 2 regulates calcification by activating matrix Gla protein, which prevents vascular calcification, and growth arrest-specific 6, which affects vascular smooth muscle cell apoptosis and movement [ 21 ]. In the case that ABCG5/ABCG8 transports vitamin K 2 , defects in vitamin K 2 transport by ABCG5/ABCG8 may be associated with the progression of atherosclerosis in addition to cholesterol transport impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Pentosidine is one of the components of AGEs. VK2 is considered to be related to vascular function in recent years ( 18 , 19 ), in addition to the role of the latest inhibitor of ferroptosis ( 20 ). We evaluated the previous the oxidative stress indicators in the intestinal tissue, serum and the previous vascular endothelial factors in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on vitamin K effects in cardiovascular events have shown that a diet rich in foods containing this micronutrient may reduce atherosclerotic cardiovascular disease [ 175 ]. Its implication in the cardiac and vascular pathology is due to role played in the matrix Gla protein activation, an extrahepatic γ-carboxyglutamate protein that was found to be the most potent vascular calcification inhibitor [ 176 ].…”
Section: Potential Role Of Nutrition In Prevention Of Cardiovascular ...mentioning
confidence: 99%